Micarande: festa do povo? - Pereira Filho, Sebastião Faustino (2006)
Contemporary politics have assumed new configurations both in the way they are carried out and in the content publicized. Nevertheless, some practices are unchanged since antiquity. But the advent of the media and its circumstantial molding of current society have forced politics to make some changes to adapt both to mass media and to the new social practices in liberal democracy. Given that fact, this study tried to demonstrate how power has become personalized in Campina Grande, Paraíba, Brazil, by a politician named Cássio Cunha Lima. Through the communications media and popular manifestations, he has been trying to create a symbiosis between Micarande a Carnival party (not held in the traditional Mardi Gras week) and his own public image, elaborating a process that identifies him with that event. In that way, he hopes to appropriate the festival and project his political image by using the party as na electoral currency in his publicity campaigns